Genic rather than genome‐wide differences between sexually deceptive Ophrys orchids with different pollinators. Issue 24 (27th November 2014) - Sedeek, Khalid E. M.; Scopece, Giovanni; Staedler, Yannick M.; Schönenberger, Jürg; Cozzolino, Salvatore; Schiestl, Florian P.; Schlüter, Philipp M.
Abstract High pollinator specificity and the potential for simple genetic changes to affect pollinator attraction make sexually deceptive orchids an ideal system for the study of ecological speciation, in which change of flower odour is likely important. This study surveys reproductive barriers and differences in floral phenotypes in a group of four closely related, coflowering sympatric Ophrys species and uses a genotyping‐by‐sequencing (GBS) approach to obtain information on the proportion of the genome that is differentiated between species. Ophrys species were found to effectively lack postpollination barriers, but are strongly isolated by their different pollinators (floral isolation) and, to a smaller extent, by shifts in flowering time (temporal isolation). Although flower morphology and perhaps labellum coloration may contribute to floral isolation, reproductive barriers may largely be due to differences in flower odour chemistry. GBS revealed shared polymorphism throughout the Ophrys genome, with very little population structure between species. Genome scans for FST outliers identified few markers that are highly differentiated between species and repeatable in several populations. These genome scans also revealed highly differentiated polymorphisms in genes with putative involvement in floral odour production, including a previously identified candidate gene thought to be involved in the biosynthesis of pseudo‐pheromones by the orchid flowers. Taken together, these data suggest that ecological speciation associated with different pollinators in sexually deceptive orchids has a genic rather than a genomic basis, placing these species at an early phase of genomic divergence within the 'speciation continuum'.